Pegylated Oleic Acid-Lecithin Liposomes (Poll) for Anticancer Drug Delivery - Eh Suk, Vicit Rizal; Chung, Ivy; Misran, Misni (Penerbit Universiti Kebangsaan Malaysia, 2020)
Cancer is a major health issue, conferring to more than 14.5 million deaths worldwide. Liposomes, self-assembly amphiphilic bilayer molecules, served as excellent alternative vehicles due to their ability to encapsulate both hydrophobic and hydrophilic anticancer drugs. Conventional liposomes, comprised mainly phospholipids are cost-ineffective, unstable, and easily degraded by the external environment. In this study, we introduced PEGylated oleic acid-lecithin liposomes constructed by using C-18 monounsaturated fatty acids (oleic acid) and soy lecithin, in the presence of DOPEPEG2000 in pH7.4, above their glass transition temperature, Tg, by employing the simple thin layer lipid hydration method. FTIR spectrum of oleic acid, soy lecithin, and DOPEPEG2000 was studied. The average particle size without further mechanical interference was 1102.3 nm while the zeta potential value was -18 mV, which is compatible with the zeta potential of the red blood cell. The polydispersity index (PDI) was reduced by 46.2% with the incorporation of the DOPEPEG2000. The morphological study using OPM showed the presence of spherical shape liposomes that exhibit the birefringence effect under the light field and Maltese cross under the dark field. Encapsulation of folinic acid, methotrexate, doxorubicin, or irinotecan resulted in greater than 75% encapsulation efficiency (EE). Half-maximal inhibitory concentration, IC50, was significantly reduced in POLL as compared to free anticancer drugs. Our data demonstrate POLL may be a promising alternative vehicle to deliver various anticancer drugs to targeted tumour sites. © 2020 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.